Gender Washing Autocracies in Egypt: Drawing on the Presidency’s Of Anwar El Sadat and Hosni Mubarak - Aly, Menat (AUC Knowledge Fountain, 2023)
Research Question: The main research question this study seeks to address is: Why did the autocratic regimes of Anwar el Sadat and Hosni Mubarak choose to advance women’s rights? Hypothesis: Autocratic governments under Sadat and Mubarak used gender instrumentally, and their focus on empowering women in their societies was functional to promoting their vision of "modernization" internationally and to enhancing their image, while at the same time concealing their autocratic practices. Research Problem Authoritarian [1]systems in the Arab world have long used different tactics in order to consolidate their regimes. Indeed, one such tactic is the use of gender washing. Originally, scholars have applied this tactic in various countries where the rights of women in the community have been furthered as a mechanism to distract the narrative away from the often horrific actions of government oppression against other groups and seek to attract foreign attention to portray themselves as modernized and just regimes. In the context of this research, the concept of gender washing will be used to study how Egyptian rulers, Anwar el Sadat and Hosni Mubarak, applied this tactic to further women’s rights and to change the narrative regarding their own actions. There exists a recent trend where women in the Arab world are being empowered by the government and placed in unprecedented leadership positions. Although many scholars address the topic of Middle Eastern countries and autocratic regimes' developmental process and have explored how women's rights are being advanced, this study is going to tackle the apparent gap in analysis on why such authoritarian regimes use gestures of women empowerment in light of their modernization efforts. Additionally, there seems to be limited literature on the application of gender washing in the context of authoritarianism, women’s rights and modernization. [1] Authoritarianism is a “…political system predominantly characterized by a personalized method of rule, and in such cases, the state can be best understood as a government of men rather than law. Thus, while formal political institutions exist these, these institutions are usually devices manipulated to maximize the personal power of the rulers rather than to define and impose universally accepted rules of political conduct and constraint (Kassem, 1999, p. 3).